2018
DOI: 10.3389/fphys.2018.01245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lactobacillus casei BL23 on the Host Transcriptome, Growth and Disease Resistance in Larval Zebrafish

Abstract: In this study, zebrafish were treated with Lactobacillus strains as probiotics from hatching to puberty, and the effect of treatment with L. casei BL23 on the development and immunity response of the host was investigated. Genes that were differentially expressed (DEGs) in the overall body and intestine were detected at 14 days post fertilization (dpf) and 35 dpf, respectively, using whole transcriptome sequencing (mRNAseq). We showed that zebrafish raised by continuous immersion with L. casei BL23 showed a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…However, another previous study indicated that, microbial colonization upregulated the expression level of myd88 gene (van der Sar et al, 2006). Additionally, Qin et al (2018) found that Lactobacillus casei BL23 increased the expression of stress-related genes compared to GF zebrafish, suggesting the expression of these genes might be a self-protection mechanism of the host, which is consistent with our results on stress related genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, another previous study indicated that, microbial colonization upregulated the expression level of myd88 gene (van der Sar et al, 2006). Additionally, Qin et al (2018) found that Lactobacillus casei BL23 increased the expression of stress-related genes compared to GF zebrafish, suggesting the expression of these genes might be a self-protection mechanism of the host, which is consistent with our results on stress related genes.…”
Section: Discussionsupporting
confidence: 91%
“…The microbiota residing within the animal gastrointestinal tract play important roles in various physiological processes, including modulation of immune system (Koch et al, 2018), enhancement of intestinal barrier (Takiishi et al, 2017), absorption or digestion of nutrients (Delzenne and Singer, 2016), inhibition of pathogens (Qin et al, 2018) and host behavior and neurodevelopment (Diaz Heijtz et al, 2011; Davis et al, 2016; Phelps et al, 2017). Therefore, studies on the relationships between the host and intestinal microbiota have received more attentions in recent years (Zhao, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish immersed with Lactobacillus casei BL23 from 3-25 dpf displayed an increased survival compared to controls after an immersion challenge with Aeromonas hydrophila. Gut gene expression of il-1β, C3a, and il-10 was upregulated after 8 and 24 h after A. hydrophila challenge compared to controls (71). Interestingly, potential probiotics from the genera Lactobacillus modulated gene regulation in a strain-specific fashion.…”
Section: Probioticsmentioning
confidence: 91%
“…RNA purity was checked using a NanoPhotometer ® spectrophotometer (IMPLEN, CA, United States). RNA concentration was measured using a Qubit ® RNA Assay Kit in a Qubit ® 2.0 Fluorometer (Life Technologies, CA, United States) (Qin et al, 2018). RNA integrity was assessed using the RNA Nano 6000 Assay Kit of the Bioanalyzer 2,100 system (Agilent Technologies, CA, United States).…”
Section: Rna Extraction and Quality Assessmentmentioning
confidence: 99%